2016
DOI: 10.1038/npp.2016.93
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Modulates Fear Memory Formation Through Interactions with Serotonergic Transmission in the Mesolimbic System

Abstract: Emerging evidence suggests that the largest phytochemical component of cannabis, cannabidiol (CBD), may possess pharmacotherapeutic properties in the treatment of neuropsychiatric disorders. CBD has been reported to functionally interact with both the mesolimbic dopamine (DA) and serotonergic (5-HT) receptor systems. However, the underlying mechanisms by which CBD may modulate emotional processing are not currently understood. Using a combination of in vivo electrophysiological recording and fear conditioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 49 publications
3
62
0
Order By: Relevance
“…We have previously reported that CB1R‐mediated modulation of mesolimbic DA activity states requires local GABA A and GABA B receptor transmission within the VTA (Draycott et al., ). Thus, the ability of both intra‐PFC and intra‐NASh cannabinoid‐mediated modulation of VTA DAergic neurones has been found to require localized VTA GABA A/B receptor transmission as intra‐VTA antagonists of these receptors blocks the effects of PFC or NAc‐mediated cannabinoid modulation of the VTA and fear‐related associative memory formation (Draycott et al., ; Norris et al., ). Accordingly, we hypothesized that intra‐NASh THC administration may modulate fear‐related conditioning salience through a local GABA A/B signalling mechanism in the VTA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that CB1R‐mediated modulation of mesolimbic DA activity states requires local GABA A and GABA B receptor transmission within the VTA (Draycott et al., ). Thus, the ability of both intra‐PFC and intra‐NASh cannabinoid‐mediated modulation of VTA DAergic neurones has been found to require localized VTA GABA A/B receptor transmission as intra‐VTA antagonists of these receptors blocks the effects of PFC or NAc‐mediated cannabinoid modulation of the VTA and fear‐related associative memory formation (Draycott et al., ; Norris et al., ). Accordingly, we hypothesized that intra‐NASh THC administration may modulate fear‐related conditioning salience through a local GABA A/B signalling mechanism in the VTA.…”
Section: Resultsmentioning
confidence: 99%
“…Bilateral microinfusions were performed over 1 min with injectors left in place for an additional minute to allow adequate diffusion from the injector tip. All drug dose ranges were based upon previously published and carefully established dose–response curves for intracranial microinfusions that have demonstrated pharmacological specificity and behavioural efficacy (Laviolette, Nader, & van der Kooy, ; Laviolette & van der Kooy, ; Norris et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of conditioned fear expression by CBD in these brain areas was shown to be dependent on 5‐HT 1A receptors (Gomes et al , ; Fogaça et al , ; Marinho et al , ). The inhibitory effect of CBD on the acquisition of fear conditioning has also been shown to depend on 5‐HT 1A receptor activation in the nucleus accumbens shell (Norris et al , ).…”
Section: Pharmacological Mechanisms and Brain Sites Involved In The Ementioning
confidence: 99%
“…One study in humans showed that CBD enhanced the extinction of visual fear memory when given immediately after, but not before, extinction (Das et al, 2013). More recently it was found in rats that CBD infused into the nucleus accumbens shell impaired the encoding of olfactory fear memory, an effect blocked by 5-HT 1A R antagonism (Norris et al, 2016). To investigate this issue further we determined the effect of systemic CBD administration on the expression and extinction of auditory fear memory.…”
Section: Cbd Regulation Of Fear Memory Processing Involving Discrete mentioning
confidence: 99%